Ecophysiologie de la maturation sexuelle et de la ponte de l'huître creuse Crassostrea gigas : réponses métaboliques (respiration) et alimentaires (filtration, absorption) en fonction des différents stades de maturation - Soletchnik, Patrick; Razet, Daniel; Geairon, Philippe; Faury, Nicole; Goulletquer, Philippe (1997)
The study of sexual maturation and spawning in the Pacific oyster (Crassostrea gigas) is part of a vast research programme that endeavours to understand the causes of mortality that occur sporadically during the spring and summer seasons in the Marennes-Oléron Bay. Thermal and diet conditioning were used to obtain oysters at each stage of maturity simultaneously. Using the measured rates of clearance, consumption, absorption and respiration provided estimates of growth potential and gave the energetic budget of oysters at different stages of sexual maturity. Physiological responses were similar for males and females. Filtration decreased from 2.4 to 2.6 l.h (-1) to 1.8 l.h (-1) with increasing maturity. Weight gain was associated with gonad development and did not appear to have an effect on the clearance rate. Oysters 2.5 years old showed a negative energy budget (-15 J h (-1)) at later maturity stages. This deficit was confirmed (90 J.h (-1)) in oysters 1.5 years old at the same stage of maturity. On the contrary, immature oysters, in the early stages of maturity or post-spawning, had a growth potential of 110 to 170 J.h (-1). The energy deficit observed at later stages of maturity was primarily due to absorption, which decreased sharply during peak gametogenesis. Using measured respiration rates, an allometric relationship specific to gonad growth was determined with a coefficient of 0.574. Low physiological performance of oysters, observed at later stages of sexual maturity, must be taken into account in research on the factors responsible for spring and summer mortalities affecting oyster farms in Marennes-Oléron. L'étude de la maturation et de la ponte de l'huître creuse Crassostrea gigas, s'intègre dans une large problématique visant à comprendre les causes de mortalité qui surviennent épisodiquement dans le bassin de Marennes-Oléron au printemps et en été. Un conditionnement thermique et alimentaire des élevages permet d'obtenir simultanément des huîtres à tous les stades de maturité sexuelle. Le calcul des taux de filtration, consommation, absorption et respiration permnet d'estimer le potentiel de croissance, et donne le bilan énergétique des huîtres aux différents stades sexuels. Les réponses physiologiques sont semblables pour des huîtres mâles ou femelles. La filtration de 2,4 à 2,6 1.h(-1), passe à 1,8 1.h(-1) à un stade de maturation avancée. La prise de poids liée au développement des gonades ne semble pas avoir d'effet sur le taux de filtration. Les huîtres de 2,5 ans présentent un bilan énergétique déficitaire (-15 J.h-1) à un stade de maturation avancée. Ce déficit est confirmé (90 J.h(-1) sur des huîtres de 1,5 ans au même stade de maturation. En revanche, les huîtres immatures, en début de maturation ou en post-ponte, ont un potentiel de croissance compris entre 110 et 170 J.h(-1). Le déficit énergétique observé au stade de maturation avancée relève essentiellement de la fonction d'absorption qui chute de façon importante en période de forte gamétogenèse. L'étude de la respiration permet de définir une allométrie particulière à la croissance gonadique avec un coefficient d'allométrie de 0,574. La faiblesse physiologique des huîtres, observée à un stade de maturation avancée, doit être prise en compte dans la recherche des facteurs responsables des mortalités printanières et estivales affectant les cheptels en élevage dans le bassin de Marennes-Oléron.